Simultaneous Alcohol and Marijuana Use Among Young Adult Drinkers: Age‐Specific Changes in Prevalence from 1977 to 2016 - Yvonne M. Terry‐McElrath; Megan E. Patrick (2018)
Background The overall prevalence of U.S. young adult alcohol use has decreased, but little is known about historical change in related behaviors such as simultaneous alcohol and marijuana ( SAM ) use that may increase alcohol‐related risks and societal costs. The purpose of this paper was to examine historical change in SAM use prevalence among U.S. young adult alcohol users from 1977 to 2016, and consider the extent to which observed historical change in SAM use among alcohol users reflects co‐occurring change in marijuana use during these years. Methods Data on past 12‐month alcohol, marijuana, and SAM use at up to 6 modal ages (19/20, 21/22, 23/24, 25/26, 27/28, and 29/30) were collected from 11,789 individuals (45.0% men) participating in the Monitoring the Future panel study. Annual prevalence estimates within modal age group were obtained; historical SAM use trends among alcohol and marijuana users were estimated. Results From 2014 to 2016, SAM use was reported by approximately 30% of alcohol users aged 19/20 and 21/22, and 20 to 25% of alcohol users aged 23/24 through 29/30. Since the mid‐1990s, age‐specific historical trends in SAM use prevalence among alcohol users followed 1 of 4 patterns: significant increase followed by oscillating increases/decreases (at modal age 19/20), consistent and significant increases (at modal ages 21/22, 23/24, and 25/26), stability followed by increase (at modal ages 27/28), or stability (at modal ages 29/30). In contrast, SAM use trends among marijuana users primarily reflected stability, with some evidence of a decrease across time at modal ages 19/20 and 23/24. Historical change in SAM prevalence among alcohol users was strongly and positively correlated with changes in overall marijuana use prevalence. Conclusions A growing proportion of early and mid‐young adult alcohol users reported SAM use, with the highest risk among those in the early years of young adulthood. Young adult SAM use may continue to increase in proportion to the degree that young adult marijuana use continues to increase.